Revealing city identity through a semiotic approach: analysis of city elements - Ayub Muktiono (Journal Of Data Science, 2024)
There is generalization and uniformity in the form of development and visuals of the city, so that the city becomes increasingly foreign to society, especially in recognizing and exploring the potential of one's identity to fulfill one's life needs. A city as a complex entity is not only a physical collection of buildings, but also a system of meaning that can be described through a semiotic approach. This research aims to reveal the identity of a city through analyzing city elements using semiotic theory as a basis. A semiotic approach allows us to understand the way symbols and signs within a city contribute to the formation of its identity. The results of this research reveal that city architecture is not just a physical structure, but rather a reflection of the city's identity which is formed through careful planning, taking into account historical, local, rarity, socio-cultural, aesthetic and harmony values. Green and non-green open spaces in urban areas display various forms that reflect social interaction, providing a place for people to communicate, share experiences and build relationships. Apart from its ecological function, open space also has an important role in the social, architectural and economic aspects of cities. Thus, this research highlights the complexity of city elements and symbols in shaping identity as well as the role of open spaces as centers of social interaction, providing insights for holistic and sustainable urban planning.